Systems Thinking - Whitcomb, Cliff; Davidz, Heidi; Groesser, Stefan (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Systems Thinking Special Issue contains 12 papers on the nature of systems thinking as it applies to systems engineering, systems science, system dynamics, and related fields. Systems thinking can be broadly considered the activity of thinking applied in a systems context, forming a basis for fundamental approaches to several systems disciplines, including systems engineering, systems science, and system dynamics. Although these are somewhat distinct fields, they are bound by common approaches in regard to systems. Whereas systems engineering seeks to apply a multidisciplinary, holistic approach to the development of systems, systems science seeks to understand the basics related to systems of all kinds, from natural to man-made, and system dynamics seeks to understand system structures in order to influence its dynamics. Man-made systems have become more ubiquitous and complex. The study of systems, both natural and engineered, presents new challenges and opportunities to understand emergent, dynamic behaviors that inform the process of sense-making based on systems thinking.